Examining the Wellbeing of In-Service EFL Teachers in a Spanish Context - Carmen Carvajo Lucena; Juan Ramón Guijarro Ojeda (Universidad Nacional de Colombia, 2024)
This paper aims to extend our understanding of the factors underlying teacher wellbeing and the stress-coping mechanisms that professionals from the field use in their daily lives. The study focuses on the point of view of EFL teachers working in Andalusia, the southern region of Spain. Through semi-structured interviews and using Bronfenbrenner's ecological theory for the content analysis of data, the project identifies the primary sources of distress and growth that participants link to their profession. Key among them are emotional competence, the school environment, legislation, and boundaries. The study also pinpoints the main stress-coping strategies participants were already implementing in their lives to fight against feelings of burnout. Especially relevant is the practice of hobbies, professional training, and establishing boundaries.